2014
DOI: 10.1089/omi.2013.0140
|View full text |Cite
|
Sign up to set email alerts
|

High CYP2A6 Enzyme Activity as Measured by a Caffeine Test and Unique Distribution of CYP2A6 Variant Alleles in Ethiopian Population

Abstract: CYP2A6 metabolizes clinically relevant drugs, including antiretroviral and antimalarial drugs of major public health importance for the African populations. CYP2A6 genotype-phenotype relationship in African populations, and implications of geographic differences on enzyme activity, remain to be investigated. We evaluated the influence of CYP2A6 genotype, geographical differences, gender, and cigarette smoking on enzyme activity, using caffeine as a probe in 100 healthy unrelated Ethiopians living in Ethiopia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
(56 reference statements)
2
24
0
1
Order By: Relevance
“…Ethiopians display a distinct pharmacogenetic profile and CYP enzyme activities compared with other populations, including Caucasian, Asians, and other Black African populations. Higher CYP3A (Gebeyehu et al, 2011), CYP2A6 (Aklillu et al, 2014), CYP2B6 (Ngaimisi et al, 2013), SLCO1B1 (Aklillu et al, 2016), and CYP2D6 (Aklillu et al, 1996) enzyme activities and unique distribution of the respective variant alleles in Ethiopians compared to other populations were reported previously.…”
Section: Discussionmentioning
confidence: 58%
“…Ethiopians display a distinct pharmacogenetic profile and CYP enzyme activities compared with other populations, including Caucasian, Asians, and other Black African populations. Higher CYP3A (Gebeyehu et al, 2011), CYP2A6 (Aklillu et al, 2014), CYP2B6 (Ngaimisi et al, 2013), SLCO1B1 (Aklillu et al, 2016), and CYP2D6 (Aklillu et al, 1996) enzyme activities and unique distribution of the respective variant alleles in Ethiopians compared to other populations were reported previously.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, Koreans display higher CYP3A (Diczfalusy et al, 2008) and NAT2 enzyme activity than Swedes (Djordjevic et al, 2012). By comparing the same population living in different geographical locations, it was reported that CYP2D6 (Aklillu et al, 2002) and xanthine oxidase (Aklillu et al, 2003) activities are significantly influenced by environmental factors, but no such effect was found for CYP2C19 or CYP2A6 (Aklillu et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…This picture is beginning to change with the growing pool of pharmacogenomics research [15-17] and supportive programs such as the Pharmacogenomics for Every Nation Initiative (PGENI) that aims to integrate pharmacogenetics with the public health system of LMIC by constructing a resource for relevant polymorphisms using DNA samples from major ethnic groups that represent at least 10% of the population in LMIC (www.pgeni.org/). …”
mentioning
confidence: 99%